Forestry in Madhya Pradesh - Datta, R. N. (Indian Forester, 1954)
Madhya Pradesh comprises the former province of C.P. and Berar and fifteen ex-States which merged in 1948. Proprietory rights were abolished in 1951. All forests vest in the State. The land area is 130,272 square miles, 62,400 square miles being under forest. The Forest Department manages 46,803 square miles. It has a Chief Conservator, a Deputy Chief Conservator, five Conservators and 32 Divisional charges. The forest types are mixed, teak and sal. Teak, sal and other timbers, bamboos, lac, katha, tendu leaves, grazing and wildlife are the important forest resources. A revised forest policy has been formulated in 1952.